Contract Disclosure under External Scrutiny - Corona, Carlos; Kim, Tae Wook (The Accounting Review, 2024)
ABSTRACT We examine the effects of mandating compensation disclosure on executive incentive contracts, earnings management, firm value, and social welfare. We develop a moral hazard model with multiple principal-agent pairs facing an external monitor who allocates resources across firms to verify earnings management. With such scrutiny allocation, contracts exhibit externalities that create a coordination problem among principals. Contract disclosure enables principals to design the contract anticipating the monitor’s reaction. However, it may also exacerbate the coordination problem among principals because they do not consider externalities on other principals caused by the effects of their contract choices on the monitor’s scrutiny allocation. If internal controls are relatively weak, contract disclosure may make contracts more strongly contingent on reported earnings, increase earnings manipulation, and nevertheless increase social welfare. Contract disclosure improves firm value only if the scrutiny resources available to the monitor are not strongly constrained. JEL Classifications: C72; D62; G38; M43; M46.